Consensus Protocols in Multi-Cloud Distributed Databases: Challenges and Solutions - Phani Kiran Mullapudi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the evolution and challenges of consensus protocols in multi-cloud distributed database environments. The article explores how traditional consensus mechanisms adapt to the complexities of multi-cloud deployments while maintaining data consistency and reliability. The article analyzes three primary consensus protocols Paxos, Raft, and PBFT evaluating their performance characteristics and implementation challenges in distributed systems. Through detailed examination of network heterogeneity, performance implications, and optimization strategies, the article highlights the importance of adaptive approaches and machine learning techniques in enhancing system performance. The article also explores real-world implementations through case studies of major systems including Google Spanner, FaunaDB, and CockroachDB, providing insights into practical applications of consensus protocols in production environments. The article extends to CAP theorem implications and emerging technologies, offering a forward-looking perspective on the future of distributed consensus in multi-cloud architectures.